Professor Ts. Dr. Aida Mustapha was appointed the new UMPSA DVC R&I - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 4 June 2024 - Professor Ts. Dr. Aida Mustapha, 48, has been appointed as the new Deputy Vice-Chancellor (Research and Innovation) at Universiti Malaysia Pahang Al-Sultan Abdullah, effective from 4 June 2024.